The social imaginary culture of poverty - Duarte Mora, Jeanne Yvanova (Nómadas. Critical Journal of Social and Juridical Science, 2011)
Doors are opened, when believing, thinking, judging and devising of the men they are on real the tangent and the concrete thing; when the material is product of the immaterial thing, they begin to arise a considerable magnitude from incognitos. There am one of them here, will be that the poverty in itself has essence and substrate?, will be that the subject, the group and the society that happens through are condition; it is seen itself different from other groups?. Will be that the statistical, economic and political indicators that establish the nations as measuring (or we could say like exclusion barrier) between the men, are the creator or the relator of the poverty?. And in main lines that is and in truth exists the poverty? In order to be able to give explanation it, a teorización appears on the matter and it hopes that same the actors and subjects of investigation, of its interpretation on her.